The transformation of secondary school history curriculum in Zimbabwe, case study Zvishavane, 1990-2017. - Mucherera, Takudzwa (Midland State University, 2020)
The study was carried out in selected secondary schools in Zvishavane both in rural and urban areas. Collection of data was done with the use of primary sources and secondary sources through purpose sampling and conversation to provide richer details. The purpose for the study was to find the changes that have been taking place in the secondary school history curriculum and the rationale behind the change, what are the response from the critics in regard to the changes and the implementation process for the developed history curriculum in secondary schools. The targeted people were history teachers, the students, lecturers, parents and stakeholders in education systems and the administration. The curriculum is till the outcome of a fight and comprise. The study fully acquired that the changes that had been taking place in history curriculum lacked proper consultation especially to the expertise in history to air out their views in terms of content in the syllabus and themes which are being introduced. Lack of resources to meet up the demands of the subject is another challenge in terms of primary and secondary sources and also the issue of bias and more of being politicized rather than taken for academics.